Effects of induced rumination and distraction on mood and overgeneral autobiographical memory in adolescent Major Depressive Disorder and controls. - Park, R; Goodyer, I; Teasdale, J (2004)
BACKGROUND: In adults there is evidence that the affective-cognitive processes of rumination and overgeneral autobiographical memory retrieval may play a part in maintaining depression. This study investigated the effects of induced rumination as compared to distraction on mood and categoric overgeneral memory in adolescents with first episode Major Depressive Disorder (MDD), and the specificity of any effects to MDD. METHOD: Three subject groups; adolescents with first episode MDD (N = 75), non-depressed psychiatric participants (N = 26) and community controls (N = 33) were recruited. An experimental design was used, with repeated measures of 'in the moment' depressed mood and categoric overgeneral memory before and after rumination and distraction, induced on separate occasions and counterbalanced in order across participants. RESULTS: In adolescents with MDD, induced rumination as compared to distraction differentially increased depressed mood. There were no significant differences in this effect between full current MDD participants and those in partial remission. This differential effect was also seen in community controls but was absent in non-MDD psychiatric participants. In addition, rumination as compared to distraction increased overgeneral memories to negative cues in MDD participants, but this increase was not significantly related to mood change, and was specific to MDD, being absent in non-MDD psychiatric and community control groups. CONCLUSIONS: Experimentally induced rumination as compared to distraction increases depressed mood and negative categoric memories in adolescents with first episode MDD. These results suggest that rumination has a deleterious effect on mood and memory retrieval processes in adolescents with first episode MDD. Increased negative overgeneral memories with rumination may be a process of particular importance for adolescents with MDD rather than psychiatric disorder in general. The findings imply that strategies to interrupt ruminative processes may be helpful in minimising persistence of first episode MDD in adolescence.